1979
DOI: 10.1007/bf00397234
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid cistrons controlling synthesis and excretion of the exotoxin α-haemolysin of Escherichia coli

Abstract: The synthesis and secretion of the toxic exoprotein alpha-haemolysin of E. coli PM152 is coded by the transmissible plasmid pHly152 (41 x 10(6) dalton) as shown by the transformation of the plasmid DNA and the isolation of mutants that are specifically altered in the synthesis and transport of haemolysin. These mutants were obtained by chemical mutagenesis and insertion of the ampicillin transposon (Tn3) into pHly152. Tn3 transposition was also used for the identification and the location of the cistrons on pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
77
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 27 publications
6
77
1
Order By: Relevance
“…Kinetic studies have revealed that HlyC is consumed during the process of proHlyA activation (8). This nontypical kind of enzymatic reaction is consistent with the finding that proHlyA and HlyC are produced in nearly equimolar amounts (9,11,17). However, an acyltransferase activity must be involved.…”
supporting
confidence: 79%
“…Kinetic studies have revealed that HlyC is consumed during the process of proHlyA activation (8). This nontypical kind of enzymatic reaction is consistent with the finding that proHlyA and HlyC are produced in nearly equimolar amounts (9,11,17). However, an acyltransferase activity must be involved.…”
supporting
confidence: 79%
“…60 kDa) product confers this phenotype. Earlier studies have shown that this breakdown product of HlyA recognized by HlyA antibodies may have haemolytic activity (Noegel et al, 1979 ;Goebel & Hedgpeth, 1982 ;Nicaud et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Four genes (hlyC, -A, -B, and -D) are needed to produce the beta-hemolytic phenotype (6,24,29). HlyC activates the hemolysin structural gene product HlyA in an unknown way (23).…”
mentioning
confidence: 99%